Conditions and Types of Anchovies in the Coastal Waters of the Spelman Strait, Central Buton Regency, Indonesia - Muis, Muis; Ilimu, Edi; Pamarudin, Pamarudin; Saleh, Ramlah; Asni, Asni (Jurnal Laut Pulau: Hasil Penelitian Kelautan, 2024)
The biodiversity of the coastal waters of the Spelman Strait is a potential that needs to be preserved and protected. Anchovy fishing plays an important role in supporting the economy of fishermen's households and the potential area of Central Buton Regency as a coastal area. This research aims to classify anchovy species and the coastal waters of the Spelman Strait as an acceptable habitat for anchovies. This is the first time this assessment has been performed to evaluate the parameters of anchovy fishing in the coastal waters of the Spelman Strait. The findings obtained based on the identification found three forms of anchovy, namely (1) Stolephorus indicus, (2) Stolephorus, sp., and (3) Stelephorus commersonnii. In addition, the water parameters are subject to the appropriate criteria. The distribution of chlorophyll-a is a barometer for anchovy fishermen in the waters of the Spelman Strait to assess the fishing ground and to pick the appropriate fishing gear.